Living with dementia in a care home: facilitating participation in activities - Galof, Katarina (Frontiers in Sports and Active Living, 2025)
IntroductionIn Slovenia, about 5% of people over 65 live in care homes. Although there is no accurate data on the prevalence and incidence of dementia, the number of people with dementia is increasing, mainly due to ageing. As life expectancy increases, so does the prevalence of dementia, which poses major challenges for ageing societies, including Slovenia. It is estimated that more than 40,000 people currently live with dementia in Slovenia. Occupational therapists are integral members of care teams in care homes. Their job is to provide residents with meaningful activities and improve quality of life.AimThe aim of this study was to investigate the frequency of different methods and techniques used by occupational therapists in the care of people with dementia in care homes.MethodsAn online survey was conducted, targeting occupational therapists working in residential care facilities. The questionnaire, developed based on professional experience and knowledge of occupational therapy in such facilities, used a 5-point Likert scale (never, occasionally, often, very often, always) to assess the frequency of strategies and techniques used in dementia care.ResultsThe results showed differences in the use of therapeutic strategies. In Slovenia, occupational therapists often focus on training and enabling people with dementia to be involved in activities of daily living, while in other countries more emphasis is placed on training carers and health professionals and including people with dementia in leisure activities, including sports.DiscussionOccupational therapists play a crucial role in improving the quality of life of people with dementia. Training in this area may be inadequate, which could explain the lower integration of sports and similar activities into therapy. Another factor could be the stage of dementia at which such activities are no longer suitable without modifications. A deeper investigation into reasons for the limited use of sports in dementia care by occupational therapists is warranted. It is crucial to recognize that each person with dementia experiences physical activity differently and faces unique challenges. Occupational therapy can greatly enhance their quality of life.